2016
DOI: 10.1016/j.odw.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decreased occlusal loading during growth on the mandibular bone characteristics

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In the soft-diet group, mineralization below the molars was increased compared to the hard diet group. Analysis showed inhibited growth of the ramus in the soft-diet group (Hichijo et al, 2015). The higher mineral density in the corpus than in the ramus in rabbits was also stated in their study by de Jong et al (2013).…”
Section: The Inorganic Component Of Bones and Teethsupporting
confidence: 63%
See 2 more Smart Citations
“…In the soft-diet group, mineralization below the molars was increased compared to the hard diet group. Analysis showed inhibited growth of the ramus in the soft-diet group (Hichijo et al, 2015). The higher mineral density in the corpus than in the ramus in rabbits was also stated in their study by de Jong et al (2013).…”
Section: The Inorganic Component Of Bones and Teethsupporting
confidence: 63%
“…The grade of mineralization depends on the metabolic condition of the entire organism, not only on physical and chemical processes at the place of mineralization (Maciejewska et al, 2014). Various papers have focused on determining mandibular bone mineralization, for example, depending on its load (Tanaka et al, 2007;de Jong et al, 2013;Hichijo et al, 2015). Hichijo et al (2015) stated that the lower jaw showed a lower degree of mineralization in the ramus than in the corpus.…”
Section: The Inorganic Component Of Bones and Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…While this may not have perfect translation to the maxilla and mandible, and these bones may be just as much effected by occlusal loading as systemic exercise loading, one cannot help but observe that the most active and athletic individuals also frequently have associated adequate facial structure [22].…”
Section: Facial Bone Expansion Strategiesmentioning
confidence: 99%
“…Growth spurt process occurs during mixed dentition, around 7 to 9 years for females and 8 to 11 years for males respectively (12,13). On the other hand, external factors such as occlusal loading from food textures and intake of vitamin D from sunlight exposure may affect GA measurements (14)(15)(16). Considering the problem above, this study was conducted to identify sexual dimorphism based on GA in 2 different sample groups which have different condition in diet and environment.…”
Section: Introductionmentioning
confidence: 99%